2021
DOI: 10.1609/aaai.v35i13.17402
|View full text |Cite
|
Sign up to set email alerts
|

Learning General Planning Policies from Small Examples Without Supervision

Abstract: Generalized planning is concerned with the computation of general policies that solve multiple instances of a planning domain all at once. It has been recently shown that these policies can be computed in two steps: first, a suitable abstraction in the form of a qualitative numerical planning problem (QNP) is learned from sample plans, then the general policies are obtained from the learned QNP using a planner. In this work, we introduce an alternative approach for computing more expressive general policies wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The second that when the gripper is not empty, any action that makes H false and does not affect n should be selected. It has been shown that general policies of this form can be learned without supervision by solving a Max-Weighted SAT theory T (S, F ) where S is a set of sampled state transitions, and F is a large but finite pool of Boolean and numerical features obtained from the domain predicates (Francès, Bonet, and Geffner 2021).…”
Section: General Policies and Value Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second that when the gripper is not empty, any action that makes H false and does not affect n should be selected. It has been shown that general policies of this form can be learned without supervision by solving a Max-Weighted SAT theory T (S, F ) where S is a set of sampled state transitions, and F is a large but finite pool of Boolean and numerical features obtained from the domain predicates (Francès, Bonet, and Geffner 2021).…”
Section: General Policies and Value Functionsmentioning
confidence: 99%
“…General Policies. The problem of learning general policies has been addressed using combinatorial approaches where the symbolic domains are given (Khardon 1999;Martín and Geffner 2004;Bonet, Francès, and Geffner 2019;Francès, Bonet, and Geffner 2021), DL approaches where the domains are given too (Toyer et al 2020;Garg, Bajpai, and Mausam 2020), and DRL approaches that do not make use of prior knowledge about the structure of either domains or states (Groshev et al 2018;Chevalier-Boisvert et al 2019;Campero et al 2021). This work is a step to bring the first two approaches together along with their potential benefits.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We turn to the problem of learning sketches given a set of instances P of the target class of problems Q and the desired bound k on sketch width. We roughly follow the approach for learning general policies (Bonet, Francès, and Geffner 2019;Francès, Bonet, and Geffner 2021) by constructing a theory T k,m (P, F ) from P, k, a bound m on the number of sketch rules, and a finite pool of features F obtained from the domain predicates and a fixed grammar.…”
Section: Learning Sketches: Formulationmentioning
confidence: 99%
“…The language of sketches is powerful, as sketches can encode everything from simple goal serializations to full general policies. Indeed, the language of general policies is the language of sketches but with a slightly different semantics where the subgoal states s to be reached from a state s are restricted to be one step away from s (Bonet and Geffner 2018;Francès, Bonet, and Geffner 2021). More interestingly, sketches can split problems into subproblems of bounded width (Lipovetzky and Geffner 2012;Lipovetzky 2021) which can then be solved greedily, in polynomial time, by a variant of the SIW algorithm, called SIW R (Bonet and Geffner 2021).…”
Section: Introductionmentioning
confidence: 99%